(untitled) (Research, Society and Development, 2020)
Cattle farming has a growing activity throughout Brazil, however, the production of these ruminants is hampered by helminths, as they cause delay in the development of animals, leading to low productivity and, consequently, high economic losses. Parasitism control by gastrointestinal nematodes is performed mainly with the use of anthelmintics. The intensive use of these drugs, the use of underdoses, incorrect diagnoses and the lack of rotation of pharmacological bases have caused a serious health problem: the resistance of helminths to drugs. The OPG test is a useful, practical, fast tool that does not require animal sacrifice, which is widely used for diagnosing the disease and prescribing the correct treatment. The present study aims to present the diagnosis and chemical control of the main bovine helminths in the literature, in order to contribute to the better development of the calves, good productivity and satisfactory economic gain for the producer.